Suicide in Medical Student: How To Prevent? - Diyaz Syauki Ikhsan; Prananjaya, Bintang Arroyantri; Syarifah Aini; Puji Rizki Suryani; Verdy Cendana; Nicholas Tze Ping Pang (Faculty of Medicine, Universitas Airlangga, 2022)
ABSTRACTIntroduction: Suicide is a deliberate act to end one's life. Suicidal incidents are often found among medical students. The suicide rate among medical students is very high when compared with students of other majors. Method: This review wishes to provide a brief explanation of factors contributing to the incidence of mental health disorders among medical students along with potential management including prevention and promotion related to the situation. Results: A study in the United States stated that the prevalence of suicidal ideation in medical students was 11%, twice of the general population, while the prevalence of attempted suicide was 6.9%. Several factors related to the academic situation that contribute to mental disorders among medical students include pressure in medical education, demand for good skills, and long education time. Discussion: These factors make them prone to depression, burnout, and various emotional and mental disorders that can trigger suicide. Therefore, efforts are needed to prevent and detect the possibility of suicidal behavior. This effort must be carried out in a multidisciplinary manner. Optimizing the academic atmosphere, family involvement, the social environment, and the ability of adequate health facilities are needed.